2020
DOI: 10.3390/ijms21041523
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Small-Molecule Activators for Glucose-6-Phosphate Dehydrogenase (G6PD) Using Machine Learning Approaches

Abstract: Glucose-6-Phosphate Dehydrogenase (G6PD) is a ubiquitous cytoplasmic enzyme converting glucose-6-phosphate into 6-phosphogluconate in the pentose phosphate pathway (PPP). The G6PD deficiency renders the inability to regenerate glutathione due to lack of Nicotine Adenosine Dinucleotide Phosphate (NADPH) and produces stress conditions that can cause oxidative injury to photoreceptors, retinal cells, and blood barrier function. In this study, we constructed pharmacophore-based models based on the complex of G6PD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…At the dataset ratio Tra/Val/Test = 2:2:1, the values of mean MCC, Acc (Test), AUC, Loss (Val), Acc (Val), F, and BAC were 0.664 ± 0.162, 0.828 ± 0.087, 0.886 ± 0.058, 0.345 ± 0.088, 84.08 ± 4.08, 0.756 ± 0.100, and 0.860 ± 0.086, respectively. Although we cannot rule out random effects, it has been shown that conformational changes of molecules, which are the position and shape of key functional groups, affect the biological activity [50,51]. Further, it was reported that the energy profile in a fragment of chemical changes periodically with torsion angles [51].…”
Section: Snapshot Angles and Input Data Split Of Chemical Compounds Imentioning
confidence: 91%
See 2 more Smart Citations
“…At the dataset ratio Tra/Val/Test = 2:2:1, the values of mean MCC, Acc (Test), AUC, Loss (Val), Acc (Val), F, and BAC were 0.664 ± 0.162, 0.828 ± 0.087, 0.886 ± 0.058, 0.345 ± 0.088, 84.08 ± 4.08, 0.756 ± 0.100, and 0.860 ± 0.086, respectively. Although we cannot rule out random effects, it has been shown that conformational changes of molecules, which are the position and shape of key functional groups, affect the biological activity [50,51]. Further, it was reported that the energy profile in a fragment of chemical changes periodically with torsion angles [51].…”
Section: Snapshot Angles and Input Data Split Of Chemical Compounds Imentioning
confidence: 91%
“…Although we cannot rule out random effects, it has been shown that conformational changes of molecules, which are the position and shape of key functional groups, affect the biological activity [50,51]. Further, it was reported that the energy profile in a fragment of chemical changes periodically with torsion angles [51]. Given these reports, the depiction angles in DeepSnap may play an important role in efficient feature extraction.…”
Section: Snapshot Angles and Input Data Split Of Chemical Compounds Imentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests the standard has the lowest saturation and hence the least molecular stability. 46 In biological assays, certain compounds (PAINS: pan assay interference) yield false positive response because they have problematic structural moieties. These compounds are considered promiscuous as they are frequent hitters.…”
Section: Chemoinformatic Profile Of Ligandsmentioning
confidence: 99%
“…Calculation of pharmacological pro le estimation is important for the screening of suitable drug-like compounds in the initial stage of drug discovery and development 15 .Physiochemical properties are very important to explain the drug-likeness of a selected compounds explained by Lipinski, Ghose, Veber and Egan rule16,17 . The molecular complexity of the chemical compound is measured as number of rings and aromatic rings, the fraction of carbons that were sp3 hybridized (Csp3) present in compound18 . Novel compound LFN had presented good bioavailability, acceptable lipophilicity, molar refractivity, molecular weight and the topological polar surface area.…”
mentioning
confidence: 99%